2016
DOI: 10.1177/0194599816655976
|View full text |Cite
|
Sign up to set email alerts
|

ACS NSQIP Risk Calculator

Abstract: The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) calculator is meant to provide an estimation of perioperative risk. Our goal was to determine the clinical applicability of the calculator in major head and neck surgery. A retrospective chart review was completed for major head and neck operations performed at 1 institution from 2013 to 2014. The calculated perioperative complication risks from the ACS NSQIP calculator were compared with observed complication rates. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 5 publications
(14 reference statements)
2
23
0
Order By: Relevance
“…20 Prasad et al reviewed 98 patients who underwent major head and neck surgery, not specific to free flap, and they also demonstrated that the SRC had poor predictive value in predicting individual risk of postoperative complications. 23 Our work represents the largest cohort study to examine all outcomes of the SRC, including complications, LOS, and rehabilitation discharge in a variety of free flap reconstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Prasad et al reviewed 98 patients who underwent major head and neck surgery, not specific to free flap, and they also demonstrated that the SRC had poor predictive value in predicting individual risk of postoperative complications. 23 Our work represents the largest cohort study to examine all outcomes of the SRC, including complications, LOS, and rehabilitation discharge in a variety of free flap reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…A threshold of 0.01 was used for good calculator performance, as in previous studies of the SRC. 22,23 Calculated Brier scores were scaled for prevalence of the postoperative outcome in our population. The SRC's ability to discriminate between patients with and without corresponding complications was described with the ROC AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted to validate the use of ACSNSQIP risk prediction in head and neck cancer was published by Prasad et al [3], who found that the score did little to predict an individual patient's risk of complications but overall predicted a similar number of complications. In our study, however, a patient's individual risk and the overall incidence of complications in the cohort were both inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…The ACSNSQIP calculator has been designed for use across multiple surgical disciplines, with specific Current Procedural Terminology (CPT) codes for a variety of surgeries. External validation for head and neck surgery has been limited, with only a few studies available in published literature [3,4], neither of which found the calculator reliable.…”
Section: Introductionmentioning
confidence: 99%
“…We selected the “1 = no adjustment necessary” label, which has been used in several publications across surgical specialties. 15 , 30 , 31 Further research is required to determine which surgeon-selected adjustment is best suited for this particular patient population.…”
Section: Discussionmentioning
confidence: 99%